Long-Term Survival of Enterococcus faecium under Varied Stabilization and Cell Immobilization Conditions - Galuza, O. A.; El’-Registan, G. I.; Kanapatskiy, T. A.; Nikolaev, Yu. A. (Microbiology (New York), 2024)
Lactic acid bacteria (LAB) play an essential role in biotechnology and biomedicine. However, their main disadvantage is the rapid death of their cultures and preparations during storage. Research on techniques of prolonging the survival time of lactic-acid bacteria under varied conditions is an important task that constituted the goal of the present work. The research subject was the lactic acid bacterium Enterococcus faecium . It was revealed that bacteria in aging planktonic cultures were rapidly losing viability (the viable cell number decreased by 2 to 4 orders of magnitude within 1 month). Under these conditions, the development cycle of the E. faecium population led to formation of cyst-like dormant cells of two different types, L forms and hypometabolic cells. Applying chemical stabilizers such as humic substances increased the viable cell number 2–3-fold. Surface immobilization (adsorption) on organosilanol or inorganic carriers such as silicon dioxide enabled elevating the number of starvation-surviving cells 1.25- to 3-fold. The most efficient approach was cell immobilization in silanol–humate gels that resulted in increasing the surviving cell number up to 35 times compared to the control. The data obtained provide an insight into the mechanisms of LAB survival and the forms of survivors under natural conditions, including the hypometabolic state and the presence of specialized dormant forms. These data can be utilized for developing techniques of long-term storage of LAB biopreparations.